FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA HIPERTENSI PADA IBU HAMIL DI WILAYAH KERJA UPT PUSKESMAS WOSU KECAMATAN BUNGKU BARAT KABUPATEN MOROWALI - Tetti Surianti; Ruslang Ruslang; Rosdiana Rosdiana (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2021)
Abstract Hypertension in pregnancy is a gestational blood pressure of 140/90 mmHg or more during pregnancy, pregnant women who experience hypertension syringe 20 weeks gestation. Hypertension in pregnancy can cause morbidity / pain in pregnant women (including seizures, this study aims to see the relationship between history of hypertension, exposure to cigarette smoke, and pregnancy stress on pregnancy hypertension in pregnant women in the work area of ​​UPT Puskesmas Wosu, West Bungku Barat, Morowali Regency. This study used an observational study with a cross-sectional study design approach. The population in this study was 30 pregnant women. The sampling technique used was total sampling. Data collection was obtained using a questionnaire. Analysis of the relationship using the chi square test. The results showed that 30 respondents (100.0%) had hypertension. The results of statistical tests showed that age (p = 0.000), history of hypertension (p = 0.002), exposure to cigarette smoke (p = 0.000), and pregnancy stress (p = 0.001). So besides that there is a relationship between age, history of hypertension, exposure to cigarette smoke and pregnancy stress with the incidence of hypertension in pregnant women in the Wosu District UPT Puskesmas Work area. West Bungku District. Morowali. Thus, pregnant women who suffer from pregnancy hypertension are expected to continue to control their health, one of which is blood pressure that remains normal. Keywords: Hypertension, Pregnancy